Hubungan Kualitas Pelayanan Kesehatan Dengan Kepatuhan Kunjungan Ibu Balita Di Posyandu Balita Makarti 4 - Mustakim, Mustakim; Marchamah, Dwi Nur Siti (Universitas Ivet, 2025)
The importance of basic health services is because posyandu plays an important role in reducing maternal and infant mortality rates. The research aims to analyze the relationship between the quality of health services and compliance with visits by mothers of toddlers at Posyandu Balita Makarti 4. The research uses a quantitative analytical design, and correlational description with a cross-sectional design. The population includes all visits by mothers of toddlers in Sumowono, Semarang Regency, in June 2023. Sample selection used a total sample of 34 respondents. The validity test uses the product moment formula, the reliability test uses Cronbach's alpha formula, the normality test uses the Shapiro-Wilk formula, and the data is analyzed using chi-square. The research results show that the service quality of Posyandu Balita Makarti 4 is considered good. The dimensions of health service quality which include tangibles (0.003), reliability (0.01), responsiveness (0.015), assurance (0.001), and empathy (0.001) show that they have a positive and significant relationship with compliance with visits by mothers of toddlers at Posyandu Balita Makarti 4. Research suggestions emphasize the importance of improving the quality of services at Posyandu as an effective strategy to increase participation and compliance with visits by mothers of toddlers.